The importance of recovering body awareness in post-stroke rehabilitation: insights from clinical case reports - Cardile, Davide; Lo Buono, Viviana; Corallo, Francesco; Cammaroto, Simona; Formica, Caterina; Quartarone, Angelo; Calabrò, Rocco Salvatore (Frontiers in Neurology, 2024)
IntroductionBody awareness (BA) is the process of gaining sensory awareness based on the physiological states and actions of the body. It is influenced by an individual’s attitudes, perceptions, beliefs, and experiences within the social and cultural contexts. Following a stroke, impairments in BA are thought to be widespread and could have a significant impact on recovery results. Regaining body awareness, however, is often neglected in the neurorehabilitation field. This study aimed to assess body image perception in two stroke patients and the potential effect of motor and cognitive rehabilitative treatments on possible improvement of BA.MethodsPatients were evaluated through a multidimensional neuropsychological assessment before and after a 3-month motor and cognitive rehabilitative training. Sessions were scheduled 6 times per week with a total duration of 3 h per session.ResultsAfter the neurorehabilitative treatment, both patients showed an improvement in BA, cognition, mood, and motor skills. Differences emerged related to the progression and improvement of their respective performances.DiscussionThe causes of these differences could include the following: different brain areas affected, the ischemic or hemorrhagic nature of the stroke, age, and sex. Further research is needed to better understand the differences and similarities in the correlations between deficit and lesional sites. Structured and early multidisciplinary intervention can certainly guarantee a better functional recovery for patients after a stroke. However, in this study we show how complementary assessment methods (such as human figure drawing) may be highly informative in choosing treatment modalities and verifying rehabilitation outcomes.